THE USE OF METAL AND PLASTIC WASTES IN THE TEACHING OF MUSIC IN EARLY CHILDHOOD SETTING - Nugroho, Agustinus Arum Eka (Indonesian Journal of Early Childhood Education Studies, 2012)
The teaching of simple musical production is one of common practice in Indonesian early childhood education. This however is accompanied by the fact that most Indonesian early childhood centers has no ability to provide musical instrument to supports their childrenâs learning.Â  ConsideringÂ  thatÂ  exposureÂ  toÂ  musicÂ  is essentially importanceÂ  toÂ  encourage childrenâs sense of aesthetics the Semarang Universityâs Department of EarlyChildhood Education initiated a short course on the teaching of music to young children for the teachers of disadvantaged centers. Unlike typical course on music, in this short course plastic and metal wastes were used to substitute musical instruments. The wastes were those, which can produce the sound of percussions, such as used water gallons, jerrycans, and metal biscuit cans. Percussions are chosen considering the fact that the teaching of music in Indonesia is combined with fine motor development stimulation. In addition, percussion is much simpler for children to play compared to others. At the end of the short course, the department has learnt that not only the program has given an alternative for the teachers of how to teach music to their children, but also has giventhem much confidence to do that. On the other hand, even though the use of plastic and metal wastes were also an emergency exit strategy, somehow the teachers have learnt to not depend on the ârealâ, mostly expensive musical instruments amidst the lack of financial support. This has also allowed teacher to not ask for more money from theparents.